TRANSFORMASI ORGANISASI PENYEDIA JASA LAYANAN JAMINAN KESEHATAN (Studi Tentang Transformasi PT. Askes (Persero) Menjadi BPJS Kesehatan) - Department, administratio; Kurniawan, Bayu; Maarif, Syamsul (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. Health insurance is a necessity that must be owned by the community ascitizens. After the demands of the changing times and other factors, then governmentdecided to transform PT. Askes (Persero) to BPJS Kesehatan by the Regulation of SJSN andthe regulation of BPJS. The transformation causes changes in the health insurance systemin Indonesia. This study aims to determine the reasons or factors that encourage theimplementation of the transformation, stages of transformation that is passed by PT.Askes (Persero) to be BPJS Kesehatan, and change what happened. The research is aqualitative study using a descriptive approach, data collection techniques used areliterature. The conclusion from this study is there are two factors that underlie theimplementation of the transformation of PT. Askes (Persero) to BPJS Kesehatan, thefactors are domestic and international factors. Domestic factors is complaints from thepublic, and the international factor is the intervention of foreign parties. Thistransformation then passes through three stages namely unfreezing, movement, andrefreezing. In each of these stages there are some changes implemented steps ofachieving the respective stages. transformations that occur in the PT. Askes (Persero)caused a lot of changes, including: changes in goals, culture, technology, organizationalstructure, and the volume of activity. Keywords : Health Insurance, Transformation, Public Agency